Ritualizing Nonreligion: Cultivating Rational Rituals in Secular Spaces. (15th May 2022) - Frost, Jacqui
Abstract: As the religious landscape in the United States continues to change, and as more Americans leave organized religion, scholars have raised important questions about the role of ritual in secular spaces and whether or not religious decline will result in a decline in meaningful ritual practices. As ritual is often conflated with religion, it is often also assumed that nonreligious people are uninterested in rituals because they are committed to science, rationality, and materialism. And many believe this means that the nonreligious live "disenchanted" lives with no means for experiencing greater meaning, transcendence, or spirituality. Drawing on an ethnographic case study of ritual creation at a secular congregation called the Sunday Assembly, I disrupt these presumed dichotomies between rationality/ritual and science/spirituality. I show how atheists and agnostics at the Sunday Assembly are secularizing religious rituals, as well as creating new secular rituals, by relying on the scientific method and a trial-and-error approach to ritual creation. In doing so, they are producing experiences of transcendence, collective effervescence, and "secular spirituality." And I show how these "rational rituals" are often seen by nonreligious people as being more meaningful than religious rituals because of the work that goes into their creation. I argue that the Sunday Assembly is an illustrative case for shedding new light on the ritual creation process, and my findings contribute to discussions about how nonreligious people negotiate what many assume are conflicting discourses of science and religion as they create meaningful secular rituals.